Theoretical analysis of interference suppression in a radiometric receiver - Гуцол, Т.Д.; Косуліна, Н.Г.; Семенець, В.В.; Носова, Т.В. (Radiotekhnika, 2019)
The subject of this article is theoretical substantiation of the adaptive algorithm of out-of-band interference suppression. The substantiation is based on the method of signal isolation from the background of additive interference. The essence of the method is to pass a mixture of signal and interference through a filter in which interference is suppressed while the signal practically does not change. The method of minimum mean square error was used to estimate the efficiency of the scheme of the additive compensator for out-of-band interference and to calculate the output signal-to-interference ratio.